Determinan innovative work behavior generasi Z: dengan grit sebagai pemoderasi - Yanuar Surya Putra; Hardi Utomo; Ambar Istiyani (Journal of Business & Banking, 2024)
Generation Z is a new worker demographic beginning to dominate the workplace. This study aims to investigate and explain the impact of workplace ostracism and job stress on innovative work behavior among Generation Z employees in Salatiga, using grit as a moderating variable. Companies are also anticipated to become aware of the inﬂuence of workplace ostracism and job stress on Gen Z employees’ grit and innovative work behavior, allowing them to develop HR management methods to foster innovative work behavior from Gen Z employees. The study was conducted in Salatiga, with 366 samples from Generation Zrespondents. The analysis technique employed was Moderating Structural Equation Modeling with SmartPLS. The fndings of this study indicate that grit can be a variable that reduces the negative impact of workplace ostracism and job stress on the innovative work behavior of Gen Z employees, implying that to foster innovative workplace behavior, companies must also be able to encourage high grit in their employees, particularly Gen Z employees. Managers must be able to educate employees on the value of grit in establishing long-term success and innovative work behavior.